Effect of Organic Manures and Bio-fertilizers on Yield and Fruit Quality of Banana cv. Grand Naine (AAA) - Hema, R.; Bhagavan, B. V. K.; Sudhavani, V.; Umakrishna, K. (International Journal of Bio-resource and Stress Management, 2023)
An attempt was made to study the effect of certain organic manures (vermicompost, farmyard manure, poultry manure, ash and neem cake) and bio-fertilizers (Azospirillum, T. harzanianum, arbuscular mycorrhizal fungi and phosphate solubilizing bacteria) on yield and fruit quality of banana cv. Grand Naine in comparision with T11 (200 g N+50 g P+200 g K) and control (N0+P0+K0). Yield characters viz., hands bunch-1, fruit length, fruit girth, bunch weight, yield ha-1 were higher in treatment T11 and among organic treatments,T4-FYM (15 kg)+NC (1.875 kg)+VC (7.5 kg)+Ash (9.94 kg) recorded higher yield attributes. Organic treatment T4 was recorded with highest fruit quality characters viz., total soluble solids, reducing sugars, non reducing sugars, higher shelf life and recorded higher ratings in organoleptic evaluation among all the treatments. T11 was recorded with higher pulp to peel ratio followed by T4. The utilization of organic manures and bio-fertilizers are considered as promising alternative for chemical fertilizers, especially for developing countries. Organic fertilization is another option for supplying nutrient elements to banana production. The organic materials improve soil structure and reduce soil temperature, resulting in better root growth and more efficient use of water and nutrients. Organic production of Grand Naine improves soil health, yield of crop, fruit quality viz. fruit taste, colour, keeping quality of the fruits than conventionally produced fruits. Higher profits were realized under organic banana production.